MENGALAH: Manajemen Konflik Pada Suku Dayak - Kumpiady Widen (FKIP, Universitas Palangka Raya, 2024)
This writing discusses the concept of Mengalah among the Dayak of Central Kalimantan in its relation with conflict. Mengalah is not coward, but the Dayak’s glorious nature to avoid any conflicts. Mengalah is the form and expressions of cultural values inherited from their ancestors. The concept of belief system of the Dayak contains two principles: belief in the One God and ancestor’s spirit that has directed them to keep the harmony of Cosmos in order that the Dayak’s live is prosperous and peaceful. In regarding with this belief system, the essential meaning of live of the Dayak lies on the harmony of Cosmos, it does not lie on prosperity and reality or objectivity understood by modern or scientific ideas. Maintaining the harmony of Cosmos, human being according to the Dayak, have to adhere to customs that has directed human being to keep harmony relation with the One God, with ancestor spirits, with other human beings and with the surrounding nature.